Can goal-setting for patients with multimorbidity improve outcomes in primary care? Cluster randomised feasibility trial. Issue 6 (3rd June 2019) - Ford, John A; Lenaghan, Elizabeth; Salter, Charlotte; Turner, David; Shiner, Alice; Clark, Allan B; Murdoch, Jamie; Green, Carole; James, Sarah; Koopmans, Imogen; Lipp, Alistair; Moseley, Annie; et al.
Abstract : Introduction: Goal-setting is recommended for patients with multimorbidity, but there is little evidence to support its use in general practice. Objective: To assess the feasibility of goal-setting for patients with multimorbidity, before undertaking a definitive trial. Design and setting: Cluster-randomised controlled feasibility trial of goal-setting compared with control in six general practices. Participants: Adults with two or more long term health conditions and at risk of unplanned hospital admission. Interventions: General practitioners (GPs) underwent training and patients were asked to consider goals before an initial goal-setting consultation and a follow-up consultation 6 months later. The control group received usual care planning. Outcome measures: Health-related quality of life (EQ-5D-5L), capability (ICEpop CAPability measure for Older people), Patient Assessment of Chronic Illness Care and healthcare use. All consultations were video-recorded or audio-recorded, and focus groups were held with participating GPs and patients. Results: Fifty-two participants were recruited with a response rate of 12%. Full follow-up data were available for 41. In the goal-setting group, mean age was 80.4 years, 54% were female and the median number of prescribed medications was 13, compared with 77.2 years, 39% female and 11.5 medications in the control group. The mean initial consultation time was 23.0 min in the goal-setting group and 19.2 in the control group. Overall 28% of patient participants had no cognitive impairment. Participants set between one and three goals on a wide range of subjects, such as chronic disease management, walking, maintaining social and leisure interests, and weight management. Patient participants found goal-setting acceptable and would have liked more frequent follow-up. GPs unanimously liked goal-setting and felt it delivered more patient-centred care, and they highlighted the importance of training. Conclusions: This goal-setting intervention was feasible to deliver in general practice. A larger, definitive study is needed to test its effectiveness. Trial registration number: ISRCTN13248305 ; Post-results.